Chapter «Il cybernauta è naufragato». Rappresentazioni del tecnologico nell'opera di Claudio Magris - Rebora, Simone (Biblioteca di Studi di Filologia Moderna, 2021)
This essay traces and analyses the various representations of technology in Claudio Magris' work. From the answering machines of Le voci to the war machines of Non luogo a procedere, a controversial and conflicting relationship has always been established between the protagonists of Magris' narratives and the various declinations of technological progress. The essay explores the concepts of cognitive sciences and digital humanities (such as the "extended mind" and word embeddings), while also referring to Magris' own reflections on writing and figureheads, to illustrate the profoundly ethical value of the relationship established between human beings and the tools that they create.